Personal Data Protection Analysis : Comparison of Indonesia, the United States as Federal Countries - Sevy Septiana Afina; Rina Arum Prastyanti (International Journal of Law, Crime and Justice, 2025)
Personal data protection is a crucial issue in the digital era, which is characterized by the processing and widespread dissemination of information on the internet. In this context, the different legal approaches between Indonesia and the United States raise questions regarding the effectiveness and scope of privacy protection in each country. The focus of this research is to analyze the legal systems applicable in both countries to identify the strengths, weaknesses, and potential for cross-system policy adoption. Using a normative juridical method and a comparative law approach, analysis is conducted on key regulations such as Law No. 27 of 2022 in Indonesia as well as various sectoral regulations in the United States. The findings show that Indonesia has integrated regulations but faces challenges in implementation, while the United States has more established enforcement despite its sectoral and fragmented nature. The synthesis of these two approaches emphasizes the importance of finding a balance between regulatory comprehensiveness and enforcement effectiveness. In conclusion, efforts to strengthen personal data protection in Indonesia can be directed towards strengthening institutions and oversight, while the United States can draw lessons from its centralized regulatory model to improve consistency of protection across sectors.